Decreased Morbidity and Mortality from Intestinal Ascariasis: Experience of a Single Center (Journal of Paediatric Surgeons of Bangladesh, 2014)
Background: Ascariasis is a common gastrointestinal infestation worldwide. It affects more children who live in poor hygenic condition. Pediatric surgeons are supposed to manage related surgical complications of ascariasis.Objective: To evaluate the recent pattern of occurrence of intestinal and biliary ascariasis with morbidity and mortality related to it.Materials and Methods:Study design: Retrospective study.Period of study: Study was conducted between Jan 2006 - Dec 2011 (total 06 years).Place of study: This study was carried out in the department of Pediatric Surgery, Chittagong Medical College Hospital (CMCH), Chittagong; Bangladesh.Study Subjects: Patients admitted and diagnosed as intestinal (1591) and biliary (181) ascariasis in the department of Pediatric surgery, CMCH were evaluated.Results: A total of 1772 patients were admitted with surgical complication of ascariasis. Among them 1591 (89.78%) patients were diagnosed as intestinal ascariasis and 181 (10.22%) patients as biliary ascariasis. Age range was 6 months to 12 years with mean age of 6 years for intestinal ascariasis. Biliary ascariasis presented between 3 years to 12 years with mean age of 7 years. Male (1060) suffered more than female (531). Male to female ratio was 2:1 for intestinal ascariasis while females (120)  suffered more than male(61) in biliary ascariasis ( ratio 2: 1). Total 231 surgery both elective and emergencies were done.Discussion: Most of the patients (52-81% ) were treated by endoscopic removal of worm from common bile duct. Some patients (15 - 31 %) were treated successfully by conserevative approach. Only a few patients needed open surgical procedure. No patient had died from biliary ascariasis and death from complications of intestinal ascariasis reduced from 20% to 4% over the last 6 years.Conclusion: There has been a reduced number of disease burden over the last few years from ascariatic and biliary ascariasis.DOI: http://dx.doi.org/10.3329/jpsb.v2i2.19551